Development of a technology for processing waste plastic bottles and bags to obtain various types of biodegradable polymer films (International Journal of Biology and Chemistry, 2022)
Currently, one of the most important problems in the world is waste bottles made of polyethylene terephthalate, the number of which is currently growing every hour, polluting the environment. One of the ways to protect the environment from polyethylene terephthalate waste is the invention of biodegradable polymer materials from PET waste. Currently, several methods for processing polyethylene terephthalate waste have been proposed, but the work on the production of biodegradable materials has not been fully solved. Currently, various technologies for recycling plastic bottles and bags are being developed. The most promising technology in this direction is chemical processing, which is based on obtaining the final product in the form of a monomer or oligomer, which can be used as a new raw material for the synthesis of polymers. In this work, these polyethylene terephthalate wastes were chemically degraded with ethylene glycol solvent in the presence of zinc acetate catalyst and bis-hydroxy ethylene terephthalate was obtained. This work aims to obtain bis-2-hydroxyethyl terephthalate (BHET) by glycolysis of polyethylene terephthalate (PET) waste for the synthesis of various types of biodegradable polymer films. Biodegradable films based on polyvinyl alcohol and BHET have been synthesized. Water-soluble copolymers based on BHET and PVA were obtained by grafted copolymerization. (PVA) polyvinyl alcohol (5; 15; 25 wt. %) was dissolved in distilled water at 75-80°C until complete dissolution, ammonium persulfate, used as an initiator, was added to the initial mixture and biodegradable films based on PVA and BHET were obtained for the first time.  It has also been proved that the resulting biodegradable films are formed by hydrogen bonds using IR spectroscopy.